From fields to cities: Innovating assessment of soil quality in Southern Iran’s Urban areas - Sayyed Mahmoud Enjavinezhad; Seyed Javad Naghibi; Morteza Poozesh Shirazi; Majid Baghernejad; María Fernández-Raga; Jesús Rodrigo-Comino (PLoS ONE, 2025)
Evaluation of soil quality in urban and peri-urban areas using comparable and reproducible indexes is a necessary step to assess the soil management status and its potential for different uses. The application of quantitative indexes guarantees neutrality and reliability of results, allowing comparisons between areas with similar environmental soil conditions. However, there is no consensus on the application of specific indexes. Therefore, in this research, three indexes (Integrated, Weighted Integrated, and Nemoro´s quality indexes) and two approaches (linear and non-linear methods) were compared to select the most relevant soil properties for evaluating soil quality for different land uses (e.g., agriculture, gardening, parking, rangelands, or bare areas). To this end, an experimental area was selected with a total dataset of 25 physicochemical and biological properties in the Shiraz urban watershed (southern Iran). Nine soil properties were selected using the principal component analysis method as the most informative factors, forming the minimum dataset. The results showed that gardens and bare land had the highest (SQI = 0.34–0.55 across different approaches) and lowest soil quality index (SQI = 0.25–0.44 across different approaches), respectively. The non-linear index calculation approach had better efficiency than the linear one. According to the coefficients of determination (R2 = 0.81–0.89), these key soil variables were suggested as a solution to reduce both the cost and time required for projects carried out by experts and watershed decision-makers to assess soil quality in urban and peri-urban areas.